Modified specific gravity method for estimation of starch content and dry matter in cassava - Kanvisit Maraphum; Khwantri Saengprachatanarug; Seree Wongpichet; Arthit Phuphuphud; Panmanas Sirisomboon; Jetsada Posom (Heliyon, 2021)
of 0.96. To confirm that the empirical model was effective when applied to other samples, unknown samples collected from another area were tested, and the results showed a standard error of prediction (SEP) of 1.02%FW and 3.49%, mean different (MD) of -0.66%FW, -0.89% for the SC and DM, respectively. Hence, our empirical equation based on a modified SG method could be used to estimate the SC and DM in cassava tubers. It can help breeders to reduce costs and time requirements. Moreover, breeders could be used the methods to evaluate the SC and DM from the tuber formation to harvesting stage and monitoring the changes in SC and DM during breeding.
Keywords: Cassava research and cyanide; Sesame and Sesamin Research; Food composition and properties